Brainstorming Business Model Canvas Pada Formulasi Strategi Optimalisasi Sedimentasi Tailing Tambang Emas Pada Pertambangan Emas Skala Kecil di Koperasi Produsen Tombang Tujuah Loge - Yusriwarti, Yusriwarti; Alpiyandri, Alpiyandri; Zulfhi Surya, Roberta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Alluvial gold mining tailings in Logas consist of sand and mud, which are dominated by silica minerals and feldspar; the fine sand size fraction and the picking fraction are dominated by silica minerals, metals, and other high-hardness minerals. Tailings pose a new problem, namely sedimentation, which results in the silting of rivers, which causes flooding and damages community plantations. Tailings still have economic value, which can provide a source of income for the Tombang Tujuah Loge Producers Cooperative. This study formulates the idea of "stakeholders" so that all parties can participate in planning their business strategies. The Brainstorming Business Model Canvas method is able to explore potential ideas from stakeholders who are usually reluctant to convey ideas orally. The results of this study obtained the Business Model Canvas for strategy formulation regarding the development of a tailings utilization business.an bisnis pemanfaatan tailing